Bantayog : discovering Manila through its monuments - Capili, Maria Angelica A. (Metro Manila, Philippines : Foreign Service Institute, Department of Foreign Affairs, 2008)
History of Manila through the different monuments all over the city.
Includes bibliographical references (pages 70-77).
In English.